EKONOMI SIRKULAR, POLA BERFIKIR DAN PENDIDIKAN UNTUK KEBERLANJUTAN EKONOMI - Yuni Mariani Manik (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The beginnings of the Direct Economy – the ‘take-make-use-dispose’ demonstrate of utilization – date from the Mechanical Insurgency and the worldwide economy created around this demonstrate. Various social, financial and natural variables cruel that it is not economical. A radical new model – the Circular Economy – is being pushed but as however it isn't broadly practiced. This paper proposes that originators are vital to the improvement of this unused financial model; furthermore, this show encourages instruction for supportability and upgrades employabilityKeywords: Circular Economy, Education For Sustainability, Sustainable Design And Manufacturing